2015
DOI: 10.1021/cg501560z
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Architectures of [MnIICrIII(oxalate)3] Complexes with Cage-Type Networks Surrounding Supramolecular Cations

Abstract: Metal−organic network structure based on oxalate bridges {[Mn II Cr III (oxalate) 3 ] − } ∞ and supramolecular cations (H 2 PPD 2+ )(benzo[18]crown-6) 2 [MnCr(oxalate) 3 ]-(CH 3 OH)(CH 3 CN) 2 (1) and (o-FAni + ) 2 (DCH[18]crown-6) 2 [Mn(CH 3 OH)Cr(oxalate) 3 ][MnCr(oxalate) 3 ](CH 3 OH)(2), where H 2 PPD 2+ , o-FAni + , and DCH[18]crown-6 denote p-phenylenediammonium 2+ , o-fluoroanilinium + , and cis-syn-cisdicyclohexano[18]crown-6, respectively, were synthesized. The crystal structure of 1 was the combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…While the preceding nets have all been described and found in various compounds (occurrence can be checked with ToposPro) we were surprised to find a new two-nodal three-connected net noa in RUGKIP (o-FAni + ) 2 IJDCHij18]crown-6) 2 ijMnIJCH 3 OH) CrIJoxalate) 3 ]ijMnCr-IJoxalate) 3 ]IJCH 3 OH). 32 This new net has point symbols 4•8•10 and 8•10 2 and again we see the characteristic four-fold helices in a racemic set-up, but this time connected by four rings. This enforces 90°angles in the network, and this is achieved by one of the Mn ions having one mono-coordinated oxalate ion and a methanol molecule completing the octahedron.…”
Section: Tris-oxalates [M′mijox) 3 ] X−mentioning
confidence: 59%
“…While the preceding nets have all been described and found in various compounds (occurrence can be checked with ToposPro) we were surprised to find a new two-nodal three-connected net noa in RUGKIP (o-FAni + ) 2 IJDCHij18]crown-6) 2 ijMnIJCH 3 OH) CrIJoxalate) 3 ]ijMnCr-IJoxalate) 3 ]IJCH 3 OH). 32 This new net has point symbols 4•8•10 and 8•10 2 and again we see the characteristic four-fold helices in a racemic set-up, but this time connected by four rings. This enforces 90°angles in the network, and this is achieved by one of the Mn ions having one mono-coordinated oxalate ion and a methanol molecule completing the octahedron.…”
Section: Tris-oxalates [M′mijox) 3 ] X−mentioning
confidence: 59%
“…The distances between mean planes of the anionic layers was about 12 Å. Positions of manganese and chromium ions in the 2D honeycomb layer can be determined by using bond lengths between each metal ion and oxygen atoms of the oxalate ligands, with ranges of 1.9–2.0 and 2.1–2.2 Å for Cr–O and Mn–O bonds, respectively . However, all bond lengths between each metal ion and the oxygen atoms of the oxalate ligands were in the range of 2.062(6) to 2.104(6) Å, indicating some disorder on each metal site in the crystal.…”
Section: Resultsmentioning
confidence: 99%
“…In the course of study, we reported on several crystals of {[Mn II Cr III (oxalate) 3 ] – } with supramolecular cations. Although the {[Mn II Cr III (oxalate) 3 ] – } exhibited various dimensionalities in the crystals, such as 3D cage structures and typical 2D layers, these crystals tend to incorporate crystal solvent in the frameworks. The {[Mn II Cr III (oxalate) 3 ] – } networks have large pores – the size of a typical 2D honeycomb pore is 10–11 Å in diameter , .…”
Section: Introductionmentioning
confidence: 99%
“…In principle, such materials might exhibit novel physical properties such as protonic conductivity, ferroelectricity, luminescence and interesting magnetic behavior resulting from interactions between two different magnetic elements. [8][9][10][11] As far as the electrical conductivity in solids is concerned, there are generally two types of carriers: ions and electrons. Ions are relatively massive and their transport is often described by a \hopping" mechanism of the ion from site to site.…”
Section: Introductionmentioning
confidence: 99%